2015
DOI: 10.1155/2015/549798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotyping ofCryptosporidiumInfection in Pet Parrots in North China

Abstract: Cryptosporidiosis is a worldwide zoonosis caused by Cryptosporidium spp., sometimes leading to severe diarrhea in humans and animals. In the present study, 311 parrots, belonging to four species, namely, Budgerigars (Melopsittacus undulatus), Lovebirds (Agapornis sp.), Alexandrine parakeets (Psittacula eupatria), and Cockatiel (Nymphicus hollandicus), from Beijing and Weifang cities, were examined for Cryptosporidium spp. infection. Blood samples of each bird were examined using enzyme linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
18
1
1
Order By: Relevance
“…Cryptosporidiosis has been reported in more than 30 avian species worldwide, primarily causing respiratory and enteric infections in birds [ 1 , 33 ]. Cryptosporidium avium , which is naturally detected in the red-crowned parakeet ( Cyanoramphus novaezealandiae ), rosy-faced lovebird ( Agapornis roseicollis ), chicken ( Gallus gallus ), blue-fronted Amazon ( Amazona aestiva ), Mitchell’s cockatoo ( Lophochroaleadbeateri ), cockatiel ( Nymphicus holandicus ) and budgerigar ( Melopsittacus undulatus ), can also infect hens ( Gallus gallus domesticus ) and budgerigars ( Melopsittacus undulatus ) in experimental models [ 1 , 5 , 12 , 34 37 ]. In the present study, fecal examination of infected animals revealed fully sporulated C. avium oocysts in hens and ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidiosis has been reported in more than 30 avian species worldwide, primarily causing respiratory and enteric infections in birds [ 1 , 33 ]. Cryptosporidium avium , which is naturally detected in the red-crowned parakeet ( Cyanoramphus novaezealandiae ), rosy-faced lovebird ( Agapornis roseicollis ), chicken ( Gallus gallus ), blue-fronted Amazon ( Amazona aestiva ), Mitchell’s cockatoo ( Lophochroaleadbeateri ), cockatiel ( Nymphicus holandicus ) and budgerigar ( Melopsittacus undulatus ), can also infect hens ( Gallus gallus domesticus ) and budgerigars ( Melopsittacus undulatus ) in experimental models [ 1 , 5 , 12 , 34 37 ]. In the present study, fecal examination of infected animals revealed fully sporulated C. avium oocysts in hens and ducks.…”
Section: Discussionmentioning
confidence: 99%
“…avium was identified in one sample and has been described in the trachea/lung and cloaca of a cockatiel (ABE et al, 2015), the kidney and cloaca (CURTISS et al, 2015) and in fecal samples of budgerigars, Amazon parrots, cockatiels and Major Mitchell's cockatoos QI et al, 2011;NAKAMURA et al, 2014;ZHANG et al, 2015). Nardi (2015) also found low positivity (1.0%; 2/204) for C. avium in canary fecal samples.…”
Section: Fecal Samplesmentioning
confidence: 96%
“…is a recent development in China (Chen and Huang, 2007 ; Wang et al, 2008a , b , c ), genotyping and subtyping tools are now widely used in the characterization of Cryptosporidium spp. in various animals (Karim et al, 2014 ; Liu et al, 2014a , b , 2015a , b ; Ma et al, 2014 , 2015 ; Qi et al, 2014 , 2015a , b , d , 2016 ; Wang L. et al, 2014 ; Ye et al, 2014 ; Zhao et al, 2014 ; Du et al, 2015 ; Li J. et al, 2015 , 2017 ; Liu A. et al, 2015 ; Li W. et al, 2015 , 2017 ; Qi, M. Z., et al, 2015 ; Wang et al, 2015a , b ; Zhang et al, 2015a , b ; Zhao G. H. et al, 2015 ; Zhao Z. et al, 2015 ; Jian et al, 2016 ; Li F. et al, 2016 ; Li P. et al, 2016 ; Li Q. et al, 2016 ; Peng et al, 2016 ; Taylan-Ozkan et al, 2016 ; Xu et al, 2016 ; Yang et al, 2016 ; Zhang S. et al, 2016 ; Deng et al, 2017 ; Gong et al, 2017 ; Zou et al, 2017 ). The use of molecular diagnostic tools in prevalence studies has led to the identification of significant differences in the transmission of Cryptosporidium spp.…”
Section: Molecular Epidemiologic Toolsmentioning
confidence: 99%